Genomic comparisons confirm Giardia duodenalis sub-assemblage AII as a unique species - Seabolt, Matthew H.; Roellig, Dawn M.; Konstantinidis, Konstantinos T. (Frontiers in Cellular and Infection Microbiology, 2022)
Giardia duodenalis is a parasitic flagellated protozoan which infects a wide range of mammalian hosts, including humans, and is subdivided into at least eight genetic assemblages commonly thought to represent cryptic species. Molecular studies have shown that G. duodenalis assemblage A, which parasitizes humans and animals, contains several phylogenetically distinct groupings known as sub-assemblages. Molecular studies employing poor phylogenetic-resolution markers routinely recover these sub-assemblages, implying that they represent evolutionarily distinct clades and possibly cryptic species, a hypothesis which is supported by epidemiologic trends. Here, we further tested this hypothesis by using available data from 41 whole genomes to characterize sub-assemblages and coalescent techniques for statistical estimation of species boundaries coupled to functional gene content analysis, thereby assessing the stability and distinctiveness of clades. Our analysis revealed two new sub-assemblage clades as well as novel signatures of gene content geared toward differential host adaptation and population structuring via vertical inheritance rather than recombination or panmixia. We formally propose sub-assemblage AII as a new species, Giardia hominis, while preserving the name Giardia duodenalis for sub-assemblage AI. Additionally, our bioinformatic methods broadly address the challenges of identifying cryptic microbial species to advance our understanding of emerging disease epidemiology, which should be broadly applicable to other lower eukaryotic taxa of interest. Giardia hominis n. sp. Zoobank LSID: urn:lsid: zoobank.org:pub:4298F3E1-E3EF-4977-B9DD-5CC59378C80E.